Integrated Bayesian Approaches Shed Light on the Dissemination Routes of the Eurasian Grapevine Germplasm - Mercati, Francesco; De Lorenzis, Gabriella; Mauceri, Antonio; Zerbo, Marcello; Brancadoro, Lucio; D'Onofrio, Claudio; Morcia, Caterina; Barbagallo, Maria Gabriella; Bignami, Cristina; Gardiman, Massimo; de Palma, Laura; Ruffa, Paola; et al. (Frontiers in Plant Science, 2021)
The domestication and spreading of grapevine as well as the gene flow history had been described in many studies. We used a high-quality 7k SNP dataset of 1,038 Eurasian grape varieties with unique profiles to assess the population genetic diversity, structure, and relatedness, and to infer the most likely migration events. Comparisons of putative scenarios of gene flow throughout Europe from Caucasus helped to fit the more reliable migration routes around the Mediterranean Basin. Approximate Bayesian computation (ABC) approach made possible to provide a response to several questions so far remaining unsolved. Firstly, the assessment of genetic diversity and population structure within a well-covered dataset of ancient Italian varieties suggested the different histories between the Northern and Southern Italian grapevines. Moreover, Italian genotypes were shown to be distinguishable from all the other Eurasian populations for the first time. The entire Eurasian panel confirmed the east-to-west gene flow, highlighting the Greek role as a “bridge” between the Western and Eastern Eurasia. Portuguese germplasm showed a greater proximity to French varieties than the Spanish ones, thus being the main route for gene flow from Iberian Peninsula to Central Europe. Our findings reconciled genetic and archaeological data for one of the most cultivated and fascinating crops in the world.